International Risk Sharing and the Irish Economy - Bénétrix, Agustín S. (The Economic and Social Review, 2015)
This paper studies international risk sharing in Ireland during the 1970-2007 period. Following the correlation- and regression-based approaches, we confirm that Ireland belongs to the rare set of countries where risk sharing took place. We also study whether changes in consumption and income risk sharing were associated with the European integration process by looking at specific sub-periods. We find no evidence of consumption risk sharing being associated with this. However, our empirical results suggest that income risk sharing improved as Europe became more integrated.